PENGETAHUAN BERHUBUNGAN DENGAN STIGMA PADA ORANG TERKONFIRMASI POSITIP CORONA VIRUS DISEASE -19 - Ni Kadek Muliawati; Ni Luh Putu Dewi Puspawati; Ni Kadek Kembar Dani Sintaningsih (LPPM STIKES Muhammadiyah Kendal, 2021)
People who are confirmed to have Corona Virus Disease 19 (covid 19) in the community cause a stigma that can lead to discrimination. This study was conducted to determine the relationship between knowledge and stigma in people who were confirmed to be positive for corona virus disease -19 in Banjar Tegal, Bebalang Village, Bangli, Bali Province. Descriptive correlation is a type of research used with a quantitative research design. The sample is 89 people with simple random sampling technique. The instrument uses a questionnaire which is distributed online via google form. Data collection using google form with 10 questions related to knowledge and 30 questions related to stigma. Data analysis using Spearman rank with the result that the majority of knowledge in the sufficient category is 65 people (73.0%), most of the stigma is in the moderate category, namely 54 people (60.7%). Bivariate analysis obtained p value of 0.000 and r value of -0.548. There is a relationship between knowledge and stigma in people who are confirmed to be positive for corona virus disease -19 in Banjar Tegal, Bebalang Village, Bangli, Bali Province. The better the level of knowledge, the lower the stigma against people who are confirmed positive for COVID-19. The results of the study can be used as a reference for implementing health promotion programs to reduce stigma in people who are confirmed positive for the corona virus disease -19.